OP0219 TLR2 differentially mediates A-SAA induced pro-inflammatory pathways in rheumatoid arthritis. (23rd January 2014) - Rooney, P.; Gao, W.; McCormick, J.; Harty, L.; Veale, D.J.; Fearon, U.; Connolly, M.
Abstract : Background: Acute Serum Amyloid A (A-SAA) is strongly expressed in rheumatoid arthritis (RA) synovial tissue (ST) and is critically involved in regulating cell migration and invasion. In this study we examine the effect of A-SAA on Notch and chemokine signalling pathways and examine if these effects are mediated through TLR2 activation. Methods: Expression of Notch 1 IC, downstream target genes HRT1, HRT2 and ligands JAGGED 1 and DLL-4 were assessed in synovial tissue and cells by Real-Time PCR and Western blot. Human microvascular endothelial cells (HMVEC) and primary Rheumatoid Arthritis Synovial Fibroblasts (RASFC) were cultured in the presence of anti-TLR2 or IgG control antibody. IL-6, IL-8, GROα and MCP-1 were assessed by ELISA, EC activation was assessed by matrigel tube formation and invasion assays. MMP expression in HMVEC and RASFC was assessed by real-time PCR, ELISA and gelatin zymography. Results: NOTCH-1, target genes HRT 1, HRT 2 and ligands JAGGED 1 and DLL-4 mRNA was demonstrated in RA and PsA synovial biopsies. A-SAA significantly induced Notch-1 IC protein expression (p<0.05), and HRT 1 and JAGGED 1 mRNA expression (p<0.05). In contrast DLL-4 mRNA was significantly inhibited in response to A-SAA (p<0.05). A-SAA significantly induced IL-6, IL-8, GROa and MCP-1 in HMVEC and RASFC, effects which were significantly inhibited by the presence of anti-TLR2 (all p<0.05). Furthermore, A-SAA induced EC activation and invasion were inhibited by anti-TLR2 (p<0.05). Conversly the presence of TLR2 had a nominal effect on MMP mRNA and protein expression. However we observed differential effects on Notch pathway signalling components. Conclusions: TLR2 differentially mediates A-SAA induced pro-inflammatory mechanisms involved in the pathogenesis of Rheumatoid Arthritis. Disclosure of Interest: P. Rooney: None Declared, W. Gao: None Declared, J. McCormick: None Declared, L. Harty: None Declared, D. Veale Grant/Research support from: Wyeth, GSK, Abbott, Opsona, Consultant for: Wyeth, GSK, Abbott, Pfizer, Schering Plough, Centocor, Speakers Bureau: Wyeth, GSK, Abbott, Pfizer, Schering Plough, Centocor, Mundipharma, U. Fearon: None Declared, M. Connolly: None Declared